Enterprise and organizational modeling and simulation : 14th International Workshop, EOMAS 2018, held at CAiSE 2018, Tallinn, Estonia, June 11-12, 2018, Selected papers /: 14th International Workshop, EOMAS 2018, held at CAiSE 2018, Tallinn, Estonia, June 11-12, 2018, Selected papers. (2018) - Unknown
No abstract available